1993
DOI: 10.21273/horttech.3.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Onion Irrigation and Nitrogen Leaching in the Arkansas Valley of Colorado 1990-1991

Abstract: Water and nitrogen (N) are major inputs in the production of onions in the Arkansas Valley of Colorado. Because nitrates move with irrigation water, the effect of different rates of application of both N fertilizer and water on nitrate leaching were studied simultaneously. After a 2-year field study (1990-1991), it was concluded that >50 t·ha-1 of onions could be obtained without any N fertilizer when >42 ppm of nitrate nitrogen (NO3-N) were initially pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 1 publication
0
18
3
Order By: Relevance
“…Based on this 1‐yr result, the authors would not recommend this level of N fertilization with the high level of soil NO 3 –N present at onion seeding. Other studies have shown that no response to N fertilization would be expected with the high level of soil NO 3 –N present at seeding in this study (Ells et al, 1993). Assuming that the entire increased fresh weight with N application was marketable onion, the estimated value of the increased onion yield with N application in 1998 was about $3325 ha −1 based on a 5‐yr average value of onion in Colorado (Colorado Agricultural Statistics Service, 2000).…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Based on this 1‐yr result, the authors would not recommend this level of N fertilization with the high level of soil NO 3 –N present at onion seeding. Other studies have shown that no response to N fertilization would be expected with the high level of soil NO 3 –N present at seeding in this study (Ells et al, 1993). Assuming that the entire increased fresh weight with N application was marketable onion, the estimated value of the increased onion yield with N application in 1998 was about $3325 ha −1 based on a 5‐yr average value of onion in Colorado (Colorado Agricultural Statistics Service, 2000).…”
Section: Resultscontrasting
confidence: 71%
“…Onion is produced in this area with high N fertilizer rates (100–300 kg N ha −1 ) applied by growers to optimize yields without regard for soil test NO 3 –N levels (Bartolo et al, 1995, 1997). Ells et al (1993) reported no response of onion to N fertilization in southeastern Colorado and found that N was lost from the root zone with furrow irrigation.…”
mentioning
confidence: 99%
“…Onion has a shallow rooting depth (<60 cm) and requires frequent irrigation to maintain market grade and quality (Schwartz and Bartolo, 1995). High N fertilization rates, shallow water tables, and frequent irrigation to establish and maintain an onion crop all contribute to a high NO 3 –N leaching potential (Ells et al, 1993).…”
mentioning
confidence: 99%
“…japonica) followed by onion and receiving furrow irrigation. Excess applications of chemical fertilizers, furrow irrigation, and rotation with paddy rice can cause environmental concerns, such N and P leaching or runoff (Ells et al, 1993;Halvorson et al, 2008;Hayshi and Hatano, 1999). Overfertilization by onion farmers has been mainly due to poor onion root development, characterized by short, unbranched lateral roots, affecting lateral spread and degree of branching (Weaver and Bruner, 1927).…”
mentioning
confidence: 99%
“…Nutrient uptake is directly affected by available nutrients in soil. Ells et al (1993) concluded that when >42 mg·kg −1 of NO 3 -N was initially present in the top 33 cm of soil and up to 1120 mm of irrigation water was applied, bulb yields higher than 50 Mt·ha −1 could be obtained without N fertilizer. J. T.…”
mentioning
confidence: 99%